Hubungan Agama Dan Negara Studi Terhadap Pemikiran Hidayat Nataatmadja Mengenai Hubungan Islam Dan Pancasila - Erik Darmawan (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
Abstract The relationship between Islam and pancasila in Indonesia is still an unfinished issue. The attitude of Indonesian Muslims is divided into three groups. The fundamentalists reject Pancasila as the basis of the state and want Islam to formally become the basis of the state. Nationalist groups reject Islam associated with state issues. The modernist group considers that there is no conflict between Islam and Pancasila so that the Pancasila can be accepted as the basis of the state for the Indonesian nation which is predominantly Muslim. The three groups, despite having different views, however, they depart from the same assumption, namely that there are two different and independent things, namely Islam and Pancasila. The problem raised in this study is how is Islam in the thought of Hidayat Nataatmadja? How is the Pancasila in the thought of Hidayat Nataatmadja? and how is the relationship between Islam and Pancasila in the thought of Hidayat Nataatmadja? Through Pancasila which is substantively the values ​​of Islamic teachings, Indonesian Muslims build new sciences. Above the new sciences new social systems are built. With the new social systems, Muslims organize a new society. It is with this new society that has been organized in an Islamic manner that Muslims build a formal Islamic civilization without the name of Islam. With the building of Islamic civilization, Muslims can compete and outperform other world civilizations. Smart and dignified.